Isolation and identification of gram negative bacteria from Musca Spp. gut at wet market area in Kuala Pilah, Negeri Sembilan / Muhammad Asyraaf Iskandar - Iskandar, Muhammad Asyraaf (2018)
The wet market is the best place to purchase the raw material such as meat, vegetables and fishes. The moisture and wet environment was a suitably place for the Musca spp. to reproduce and can carries a lot of bacterial either resides in their gut or attached to their external bodies and legs. This research was conducted to isolate and identify the Gram negative bacteria of Salmonella spp. and Shigella spp. from the Musca spp. gut by dissecting method. The cultivation of the gut samples into differential medium of MacConkey agar (MCA) and selective media of Salmonella-Shigella agar (SSA) with an addition of biochemical test showed positive growth of Salmonella sp., Shigella sp., Citrobacter sp., Proteus sp., and Providencia sp., . Furthermore, the identification of bacteria by duplicate samples shows that Salmonella spp. is the most identified bacterial inside the Musca spp. In general, these group of Enterobacteriaceae resulted in transmissions of foodborne disease around human population due to the location of the wet market was near to the waste bin and food stall as well as shops. All of the market vendors are recommend to applied a proper hygiene care towards the shop’s area and also their waste management. Finally, a further studies can be conducted by using specific identification method such Polymerase Chain Reaction (PCR) to identifies other bacterial species might be present in the samples.